Evaluation of the Implementation of the Advanced Inhil Jaya (DMIJ) Plus Integrated Village Program in Kotabaru Seberida Village, Keritang District, Indragiri Hilir Regency - Jusman, Aprilianti; Mashur, Dadang (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The Integrated Maju Inhil Jaya (DMIJ) Plus Village Program is a flagship program of the Indragiri Hilir Regency Government. This research aims to determine the evaluation of the implementation of the Integrated Maju Inhil Jaya (DMIJ) Plus Village Program and the factors inhibiting the implementation of the Integrated Maju Inhil Jaya (DMIJ) Plus Village Program in Kotabaru Seberida Village, Keritang District, Indragiri Hilir Regency. This research method uses a qualitative research approach with descriptive research type, with qualitative data collection techniques through in-depth interviews, reviewing documents, observation and literature study, with key informants; Head of the Development and Rural Areas Division of Indragiri Hilir Regency, Head of Kotabaru Seberida Village, Community Leaders of Kotabaru Seberida Village. This research uses Stufflebeam theory, namely context, input, process and product. The results of the research show that the implementation of the Advanced Inhil Jaya Village (DMIJ) Plus Integrated Program in Kotabaru Seberida Village, Keritang District, Indragiri Hilir Regency has not been implemented optimally. This can be seen from the input evaluation that there are still deficiencies such as a lack of funding and infrastructure provided. In the evaluation process, there was supervision that was not running well. Factors inhibiting the implementation of the Integrated DMIJ Plus program in Kotabaru Seberida Village are funding and lack of supervision.